Optimizing the Transparency of Madrasah BOS Funds: The Strategic Role of the East Java Regional Office of the Ministry of Religious Affairs through the E-RKAM Application - Eka Dewi, Febianita; Asrohah, Hanun (Jurnal Pengabdian Nusantara, 2025)
BOS funds are a form of government work that aims to provide equitable education and reduce the burden of education costs for students, especially in madrasahs that often face challenges in managing funds. Limited resources and the need for accountability in the use of funds are important issues that need to be addressed. The e-RKAM application is expected to improve transparency and accountability in the management of BOS funds, thereby minimizing irregularities and increasing public trust in the use of education funds. This study aims to analyse the optimization of transparency in the management of School Operational Assistance Funds (BOS) in madrasah in East Java, focusing on the strategic role of the Regional Office of the Ministry of Religious Affairs of East Java Province through the e-RKAM application. The method used is a case study with a qualitative approach. The use of various data sources, such as participatory observation, document analysis and involving in-depth interviews with madrasah managers and related parties in the Regional Office of the Ministry of Religious Affairs of East Java. The results showed that the e-RKAM application functions as an effective tool in improving transparency and accountability in the management of BOS funds. With this system, fund management becomes more structured and monitored, thus minimizing irregularities and increasing public trust in the use of education funds. In addition, the study also identified challenges faced in implementing the application, including the need for training for madrasah managers and limited access to technology in some areas. The conclusion of this study emphasises the importance of continued support from the East Java regional office of the Ministry of Religious Affairs in developing the capacity of madrasahs to maximise the benefits of BOS funds and improve the quality of Islamic education in East Java.